2022
DOI: 10.3390/su142416551
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Logistics Trends on Freight Transport Development in Urban Areas

Abstract: City logistics is subject to constant development, generated by new logistics trends and high customers’ expectations. With the aim of creating an effective, acceptable, and sustainable city logistics policy, it is therefore essential to understand logistics trends and their expected impact on the development of urban freight transport in the future. In this paper, we explore and compare the expectations of public authorities, business, and academia regarding the short-, medium-, and long-term impacts of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…There is the driver of the vehicle (or the company that operates the vehicle), and there is the E-MSP (e-Mobility Service Provider) that links the two to allow the drivers to find suitable/available charging stations and allow the CPO to charge the driver for the charging service. The E-MSP provides access to charging networks across countries [73][74][75][76][77][78].…”
Section: Resultsmentioning
confidence: 99%
“…There is the driver of the vehicle (or the company that operates the vehicle), and there is the E-MSP (e-Mobility Service Provider) that links the two to allow the drivers to find suitable/available charging stations and allow the CPO to charge the driver for the charging service. The E-MSP provides access to charging networks across countries [73][74][75][76][77][78].…”
Section: Resultsmentioning
confidence: 99%
“…New business and logistics models have the potential to change traffic patterns, impacting congestion and accidents [74,75]. The increase in delivery vehicles due to ecommerce, for example, may contribute to urban congestion [22,76]. However, innovations in logistics efficiency could mitigate this impact [77,78].…”
Section: Transport Techniques and Technologymentioning
confidence: 99%
“…Many researchers have dealt with transport issues in this region, but none of them are from the perspective of emerging trends, especially from the perspective of the business sector. It has been shown that business stakeholders have an advanced understanding of emerging technologies and their likely impacts, as well as strategic practices, which could be of great benefit for policymaking [22]. Their opinion is often not taken into account in this very demanding process.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, city centers often face limited parking spaces and narrow streets, exacerbating the problems associated with freight delivery using large vehicles. The resulting congestion and emission issues not only hinder efficient freight transportation but also impact the livability and sustainability of these urban areas [7].…”
Section: Introductionmentioning
confidence: 99%